Communication Crisis in the Tourism Sector: Tourism Village Response to Impact Climate and Weather Crisis Extreme - Bayu Suriaatmaja Suwanda; Suwanda Suwanda (Jurnal Ekonomi, 2025)
This study aims to analyze the crisis communication strategies implemented by tourism villages in responding to the impacts of the increasing climate crisis and extreme weather. The tourism sector, which is highly dependent on natural conditions, faces major challenges due to hydrometeorological disasters such as floods, droughts, and landslides. Using a qualitative descriptive approach, this study examines how tourism village managers build adaptive communication with visitors, local communities, and other stakeholders. The results of the study show that tourism village managers affected by the climate crisis and extreme weather implement crisis communication strategies based on Situational Crisis Communication Theory (SCCT), especially through the delivery of safety information (instructing information), empathy and explanation of the situation (adjusting information), and efforts to maintain a positive image by highlighting local values and environmental sustainability. This strategy is carried out despite challenges such as limited technology, low human resource capacity, and minimal cross-agency coordination. The crisis communication carried out tends to be responsive and participatory, and relies on social media and local networks to reach tourists and the community effectively.